Pengembangan Aplikasi Berbasis Android Untuk Sistem Kesejahteraan Sosial Terpadu Kesejahteraan Sosial Kabupaten Jember - Maidah, Nova El; Juwita, Oktalia; Pandunata, Priza; Zarkasi, Mohammad; Nine Amalia, Karina; M Firmansyah, Diksy (Fakultas Teknik, Universitas PGRI Banyuwangi, 2022)
Validation of the Integrated Social Welfare Data (DTKS) needs to be carried out because the government uses this data as a basis for providing various forms of social assistance. Valid data is one of the efforts so that the social assistance provided is right on target. Jember Regency is one of the districts instructed to validate the data. The University of Jember through the Institute for Research and Community Service (LP2M) is working with the Regional Government of Jember Regency to carry out DTKS validation efforts. This activity then developed an Android-based application that enumerators used to validate in the field. The data used in the application is based on data already owned by the Jember District Social Service